2011
DOI: 10.1111/j.1600-6143.2010.03421.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Preformed Donor-Specific Antibodies Following Alemtuzumab Induction and Tacrolimus Monotherapy

Abstract: It has been shown that low-level preformed donorspecific antibodies (DSAbs) detected by luminex beads in the setting of a negative CDC and flow cytometry crossmatch (CDC/FCXM) are associated with inferior allograft outcomes. The relevance of preformed DSAbs in patients receiving alemtuzumab induction and tacrolimus monotherapy has not been studied. Four hundred and eighty renal transplant recipients with a negative CDC/FCXM had their pretransplant sera retrospectively screened for DSAbs. 45/480 (9.4%) of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 42 publications
1
33
2
Order By: Relevance
“…Notably, mean and median age of the patients included with DSA-SPA tended to be similar to the age of their comparative cohort without DSA in each individual study. The types of donors included in these studies varied; two studies included only deceased-donor transplants, 5,10 one study included only living-donor transplants, 8 three studies included both donor types, 7,9,11 and one study did not describe the type of donors in the cohort. 6 Induction and maintenance regimens also varied widely across studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, mean and median age of the patients included with DSA-SPA tended to be similar to the age of their comparative cohort without DSA in each individual study. The types of donors included in these studies varied; two studies included only deceased-donor transplants, 5,10 one study included only living-donor transplants, 8 three studies included both donor types, 7,9,11 and one study did not describe the type of donors in the cohort. 6 Induction and maintenance regimens also varied widely across studies.…”
Section: Resultsmentioning
confidence: 99%
“…Gupta et al reported that no induction regimen was routinely used, whereas the other studies used antithymocyte globulin, alemtuzumab, or an IL-2 inhibitor (Table 2). [5][6][7][8][9][10][11] Two of the seven studies consistently used a steroid-free maintenance regimen, including Willicombe et al, who maintained patients on tacrolimus monotherapy. 10,11 Patel et al 8 and Verghese et al 9 maintained patients on a calcineurin inhibitor (CNI) and prednisone, whereas the Gupta, Couzi, and Higgins and colleagues used a triple-drug regimen that included a CNI, antimetabolite, and prednisone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, among patients with DSA who were transplanted following desensitization, the association between pretransplant DSA levels >5000 MFI and the likelihood of AMR was quite high (47). In contrast, a study involving Alemtuzumab-induced crossmatch negative recipients where the presence of DSA was determined retrospectively (61). In that study, the pretransplant presence of DSA was strongly associated with the likelihood of experiencing AMR.…”
Section: Single Antigen Beads Screening Beadsmentioning
confidence: 94%
“…Immunosuppression can be achieved by several mechanisms that affect lymphocytes including lymphocyte depletion, diversion of lymphocyte traffic, or blocking lymphocyte response pathways [14,15].…”
Section: Minimizing Rejectionmentioning
confidence: 99%